Taxonomic review of Chinese Phalonidia Le Marchand, 1933 (Lepidoptera: Tortricidae: Cochylini) - Sun, Yinghui; Li, Houhun (Zootaxa, 2013)
The Chinese species of Phalonidia Le Marchand, 1933 are reviewed. Sixteen species and one subspecies are treated, in-cluding three new species (P. brevifasciaria, sp. nov., P. rotundiventralis, sp. nov., and P. tenuispiniformis, sp. nov.) and three newly recorded species or subspecies (P. affinitana tauriana (Kennel, 1899), P. aliena Kuznetzov, 1966, and P. co-reana Byun & Li, 2006). The female of P. lydiae (Filipjev, 1940) is described for the first time. Images of adults and gen-italia are provided, along with a key and a distribution map for the genus in China.